A Resource-Efficient Modular Course Design for Co-Teaching Integrated Sustainability in Higher Education: Developing the Next Generation of Entrepreneurial Leaders. (January 2021) - Carey, Joanna C.; Beitelspacher, Lauren S.; Tosti-Kharas, Jennifer; Swanson, Elizabeth
Society faces mounting pressures related to economic growth, social injustice, and environmental degradation. Building upon scholarly consensus regarding the necessity of multidisciplinary approaches to address such complex problems, the entrepreneurship classroom, broadly defined, can be a learning laboratory to integrate across disciplines, encouraging more impactful opportunity identification for students looking to create social, environmental, and economically inclusive value. We examined recent exit survey data from graduating seniors at a small, private business college in the US that emphasizes entrepreneurship, finding large gaps in skills and knowledge related to ethics and creative problem solving – both of which are key competencies central to meeting the challenges of building a more sustainable world. To address these identified needs, we developed a co-taught course focused on sustainability and consumerism across liberal arts, physical science, and business disciplines. We present our course material in the context of five key competencies related to teaching sustainability in higher education, and review the strengths and drawbacks of this approach for schools looking to implement a similar design. In a time of economic uncertainty in higher education, our model may be useful for other schools looking to integrate entrepreneurship across disciplines—with little added expense to the institution.